Efficacy of Enhanced External Counterpulsation (EECP) in Nepalese chronic stable Angina patient: a single centre prospective study at Shahid Gangalal National Heart Center (SGNHC) - Adhikari, CM; Prajapati, D; Thapa, S; KC, MB (Nepalese Heart Journal, 2013)
Background Enhanced External Counterpulsation (EECP) is a novel; FDA approved; non-invasive; outpatient treatment offered to patients with refractory angina pectoris. It uses sequentially inflated pneumatic cuffs on the lower extremities to enhance coronary diastolic flow. We studied its effect in twenty one patients with refractory angina pectoris. Methods All patients (n=21) who were referred for Enhanced External Counterpulsation to Shahid Gangalal National Heart Center Enhanced External Counterpulsation Llb who completed a treatment course (one hour per day for 35 days) of EECP and underwent 6-minute walk test before and after treatment were included. Demographic data, coronary artery disease risk factors and baseline angiographic data were collected. Distance covered in six minute walk test before and after the treatment was compared. Results All the patients who had undergone Enhanced External Counterpulsation had a positive clinical response. Distance covered in six minute walk test improved in all patients after the treatment. Decrease in anginal severity, frequency and the use of sublingual nitrates, with improvement in quality of life was observed after the treatment. During the treatment some patients complained of leg pain, one patient developed blister and one ecchymosis but the treatment was not discontinued. Conclusion The results from this study suggest that Enhanced External Counterpulsation is an effective, safe and well tolerated treatment option for the patients with refractory angina pectoris. DOI: http://dx.doi.org/10.3126/njh.v9i1.8343 Nepalese Heart Journal Vol.9(1) 2012 pp.20-24